The Frequency and Associated Factors of Asymmetrical Prominent Veins: A Predictor of Unfavorable Outcomes in Patients with Acute Ischemic Stroke - Yue Wang; Jingjing Xiao; Li Zhao; Shaoshi Wang; Mingming Wang; Yu Luo; Huazheng Liang; Lingjing Jin (Neural Plasticity)
Objectives. The present study is aimed at investigating the frequency and associated factors of asymmetrical prominent veins (APV) in patients with acute ischemic stroke (AIS). Methods. Consecutive patients with AIS admitted to the Comprehensive Stroke Center of Shanghai Fourth People’s Hospital between January 2013 and December 2017 were enrolled. MRI including diffusion-weighted imaging (DWI), perfusion-weighted imaging (PWI), and susceptibility-weighted imaging (SWI) was performed within 12 hours of symptom onset. The volume of asymmetrical prominent veins (APV) was evaluated using the Signal Processing In nuclear magnetic resonance software (SPIN, Detroit, Michigan, USA). Multivariate analysis was used to assess relationships between APV findings and medical history, clinical variables as well as cardio-metabolic indices. Results. Seventy-six patients met the inclusion criteria. The frequency of APV≥10 mL was 46.05% (35/76). Multivariate analyses showed that proximal artery stenosis or occlusion (≥50%) (P<0.001, adjusted odds ratio OR=660.0, 95%CI=57.28-7604.88) and history of atrial fibrillation (P<0.001, adjusted OR=10.48, 95%CI=1.78-61.68) were independent factors associated with high APV (≥10 mL). Conclusion. Our findings suggest that the frequency of APV≥10 mL is high in patients with AIS within 12 hours of symptom onset. History of atrial fibrillation and severe proximal artery stenosis or occlusion are strong predictors of high APV as calculated by SPIN on the SWI map.